Sulfonic acid loaded self-standing covalent organic membrane for proton conduction - Sasmal, Himadri Sekhar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; Membrane; proton conduction

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Targeted drug delivery in covalent organic nanosheets (CONs) via sequential postsynthetic modification - Mitra, Shouvik; Sasmal, Himadri Sekhar; Kundu, Tanay; Kandambeth, Sharath; Math, Kavya; Diaz Diaz, David; Banerjee, Rahul (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as a new class of functional two-dimensional (2D) porous organic polymeric materials with a high accessible surface, diverse functionality, and chemical stability. They could become versatile candidates for targeted drug delivery. Despite their many advantages, there are limitations to their use for target specific drug delivery. We anticipated that these drawbacks could be overturned by judicious postsynthetic modification steps to use CONs for targeted drug delivery. The postsynthetic modification would not only produce the desired functionality, it would also help to exfoliate to CONs as well. In order to meet this requirement, we have developed a facile, salt-mediated synthesis of covalent organic frameworks (COFs) in the presence of p-toluenesulfonic acid (PTSA). The COFs were subjected to sequential postsynthetic modifications to yield functionalized targeted CONs for targeted delivery of 5-fluorouracil to breast cancer cells. This postsynthetic modification resulted in simultaneous chemical delamination and functionalization to targeted CONs. Targeted CONs showed sustained release of the drug to the cancer cells through receptor mediated endocytosis, which led to cancer cell death via apoptosis. Considering the easy and facile COF synthesis, functionality based postsynthetic modifications, and chemical delamination to CONs for potential advantageous targeted drug delivery, this process can have a significant impact in biomedical applications.

Interlayer hydrogen-bonded covalent organic frameworks as high-performance supercapacitors - Halder, Arjun; Ghosh, Meena; Khayum, Abdul M.; Bera, Saibal; Addicoat, Matthew; Sasmal, Himadri Sekhar; Karak, Suvendu; Kurungot, Sreekumar; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) have emerged as promising electrode materials in supercapacitors (SCs). However, their insoluble powder-like nature, poor capacitive performance in pristine form, integrated with inferior electrochemical stability is a primary concern for their long-term use in electrochemical devices. Keeping this in perspective, herein we report a redox active and hydrogen bonded COF with ultrahigh stability in conc. H2SO4 (18 M), conc. HCl (12 M) and NaOH (9 M). The as-synthesized COF fabricated as thin sheets were efficiently employed as a free-standing supercapacitor electrode material using 3 M aq. H2SO4 as an electrolyte. Moreover, the pristine COF sheet showcased outstanding areal capacitance 1600 mF cm(-2) (gravimetric 169 F g(-1)) and excellent cyclic stability (>100 000) without compromising its capacitive performance or Coulombic efficiency. Moreover, as a proof-of-concept, a solid-state supercapacitor device was also assembled and subsequently tested.

Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.

Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

Heterogeneous C-H functionalization in water via porous covalent organic framework nanofilms: a case of catalytic sphere transmutation - Sasmal, Himadri Sekhar; Bag, Saikat; Chandra, Bittu; Majumder, Poulami; Kuiry, Himangshu; Karak, Suvendu; Sen Gupta, Sayam; Banerjee, Rahul (Journal of the American Chemical Society, 2021)
Heterogeneous catalysis in water has not been explored beyond certain advantages such as recyclability and recovery of the catalysts from the reaction medium. Moreover, poor yield, extremely low selectivity, and active catalytic site deactivation further underrate the heterogeneous catalysis in water. Considering these facts, we have designed and synthesized solution-dispersible porous covalent organic framework (COF) nanospheres. We have used their distinctive morphology and dispersibility to functionalize unactivated C-H bonds of alkanes heterogeneously with high catalytic yield (42-99%) and enhanced regioand stereoselectivity (3 degrees:2 degrees = 105:1 for adamantane). Further, the fabrication of catalyst-immobilized COF nanofilms via covalent self-assembly of catalytic COF nanospheres for the first time has become the key toward converting the catalytically inactive homogeneous catalysts into active and effective heterogeneous catalysts operating in water. This unique covalent self-assembly occurs through the protrusion of the fibers at the interface of two nanospheres, transmuting the catalytic spheres into films without any leaching of catalyst molecules. The catalyst-immobilized porous COF nanofilms' chemical functionality and hydrophobic environment stabilize the high-valent transient active oxoiron(V) intermediate in water and restricts the active catalytic site's deactivation. These COF nanofilms functionalize the unactivated C-H bonds in water with a high catalytic yield (45-99%) and with a high degree of selectivity (cis:trans = 155:1; 3 degrees:2 degrees = 257:1, for cis-1,2-dimethylcyclohexane). To establish this approach's ``practical implementation'', we conducted the catalysis inflow (TON = 424 +/- 5) using catalyst-immobilized COF nanofilms fabricated on a macroporous polymeric support.

Covalent organic framework thin-film photodetectors from solution-processable porous nanospheres - Bag, Saikat; Sasmal, Himadri Sekhar; Chaudhary, Sonu Pratap; Dey, Kaushik; Blaette, Dominic; Guntermann, Roman; Zhang, Yingying; Poloz, Miroslav; Kuc, Agnieszka; Shelke, Ankita; Vijayaraghavan, Ratheesh K.; Ajithkumar, Thalasseril G.; et al. (Journal of the American Chemical Society, 2023)
The synthesis of homogeneous covalent organic framework (COF) thin films on a desired substrate with decent crystallinity, porosity, and uniform thickness has great potential for optoelectronic applications. We have used a solution-processable sphere transmutation process to synthesize 300 +/- 20 nm uniform COF thin films on a 2 x 2 cm2 TiO2-coated fluorine-doped tin oxide (FTO) surface. This process controls the nucleation of COF crystallites and molecular morphology that helps the nanospheres to arrange periodically to form homogeneous COF thin films. We have synthesized four COF thin films (TpDPP, TpEtBt, TpTab, and TpTta) with different functional backbones. In a close agreement between the experiment and density functional theory, the TpEtBr COF film showed the lowest optical band gap (2.26 eV) and highest excited-state lifetime (8.52 ns) among all four COF films. Hence, the TpEtBr COF film can participate in efficient charge generation and separation. We constructed optoelectronic devices having a glass/FTO/TiO2/COF-film/Au architecture, which serves as a model system to study the optoelectronic charge transport properties of COF thin films under dark and illuminated conditions. Visible light with a calibrated intensity of 100 mW cm-2 was used for the excitation of COF thin films. All of the COF thin films exhibit significant photocurrent after illumination with visible light in comparison to the dark. Hence, all of the COF films behave as good photoactive substrates with minimal pinhole defects. The fabricated out-of-plane photodetector device based on the TpEtBr COF thin film exhibits high photocurrent density (2.65 +/- 0.24 mA cm-2 at 0.5 V) and hole mobility (8.15 +/- 0.64 x10-3 cm2 V-1 S-1) compared to other as synthesized films, indicating the best photoactive characteristics.

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis